MORAL TRADITIONS AND INNOVATIONS AS A SUBJECT OF PHILOSOPHICAL ANALYSIS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article examines moral traditions and innovations as one of the key objects of philosophical analysis in the context of profound sociocultural transformation of contemporary society. Particular attention is paid to the dialectical interaction between continuity and renewal of moral values, as well as to their significance in the process of shaping individual moral consciousness and stable moral guidelines for social development. The study analyzes traditional ethical norms formed within specific historical and cultural contexts, along with new moral attitudes emerging under the influence of globalization, scientific and technological progress, digitalization, and changes in the social structure of society. The article substantiates the thesis that ignoring moral traditions or mechanically replacing them with innovations leads to a crisis in the moral foundations of social life. It concludes that philosophical reflection and a harmonious combination of traditional and innovative elements of morality are essential conditions for the spiritual development of the individual and the sustainable development of society as a whole.
Keywords: moral traditions, innovations, moral philosophy, ethics, moral values, sociocultural transformation, moral consciousness, social developmen